P04.30 Methadone does not increase toxicity of temozolomide in glioblastoma cells. (19th September 2018) - Latzer, P; Kessler, T; Sahm, F; Rübmann, P; Hielscher, T; Platten, M
Abstract: Background: Methadone is a well-known analgesic used in substitution therapy. In addition, methadone has been recently linked to cancer as it increases apoptosis and caspases activation in glioma cell lines treated with doxorubicin and it inhibits tumor growth in vivo . Although its effect on cancer is still under debate, since pro- and anti-tumoral effects have been observed and data supporting efficacy beyond casuistic reports are missing, methadone is widely used by glioblastoma patients under the assumption that it enhances the efficacy of alkylating chemotherapy. Therefore, the aim of our study is to evaluate the specific effect of methadone on glioblastoma. Material and Methods: Glioma cell lines (LN-229, A172, U87 and LN-308) as well as glioblastoma initiating cells (GIC; S24, T325, T1, L2 and T269) were treated with methadone (D/L and L; 1 μg/ml), temozolomide (TMZ) (10–300 μM) and methadone (D/L and L) + TMZ. Anti-tumor effects were investigated based on apoptosis and cell death, cell cycle arrest, proliferation and clonogenicity. Methylation of the MGMT promoter was checked with the Illumina Infinium HumanMethylation450 (450k) array. In addition, the expression of the μ-opioid receptor was analyzed by single cell analysis and immunohistochemistry on human and mouse material along with a functional assay on glioma cells. Results: The expression of the μ-opioid receptor has been faintly detected on human slices and in vitro . However, only few cells in glioblastoma patients expressed the receptor. In addition, most of the cell lines and GIC express a methylated MGMT promoter. Moreover, while there was a moderate G2 arrest of LN-229 after 6 days of treatment, 1 μg/ml methadone significantly enhanced the proliferation of T325. Furhtermore, there were no synergistic effects when combining methadone + TMZ in comparison to TMZ alone for all feature investigated in vitro . Conclusion: Methadone alone has a poor effect on glioma cells at extremely high concentration. The addition of methadone to TMZ does not provide further anti-tumoral effect compared to TMZ alone and the effect on GIC may even be adverse. Receptor expression on patient tissue is a rare exemption. The present data contrast earlier observation in A172 cells and do not support the use of methadone as a chemotherapy-enhancing agent in glioblastoma patients outside controlled clinical trials.